IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA BANK SYARIAH DI INDONESIA - Nona Azzahra Nasution; Tri Ibnu Ramadhanu; Nurul Fadilah; Ahmad Wahyudi Zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
: This study analyzes the implementation of Good Corporate Governance (GCG) principles in Indonesian Islamic banks through qualitative document analysis of annual reports from BSI, BJB Syariah, and BCA Syariah for 2022-2025. Findings reveal GCG implementation at "Good" level (average score 3.20/4.0) with transparency (3.42) and fairness (3.35) as main strengths driven by BSI's digital disclosure platform (92% index), while DPS independence (2.85) emerges as critical systemic weakness (77% average vs POJK 100% target) due to BJB Syariah's Commissioner-DPS dual position and BUMN intervention in BSI. BSI leads (3.40) through Rp780T scale economy, BCA Syariah sets independence benchmark 100% (3.20), and BJB lags (3.00) due to regional capacity constraints. Results confirm agency theory that GCG is essential to prevent profit-sharing moral hazard, recommending POJK 55/2016 Article 15 enforcement, digital GCG mandate, and national sharia HR capacity building for 3.5 score target (2027).